Coding and decoding stray magnetic fields for multiplexing kinetic bioassay platform. Issue 24 (4th November 2020) - Liu, Yuan; Lin, Gungun; Chen, Yinghui; Mönch, Ingolf; Makarov, Denys; Walsh, Bradley J.; Jin, Dayong
Abstract : The stray magnetic fields of hierarchically-assembled magnetic beads are utilised to code and decode information for multiplexed kinetic assays. Abstract : Polymer microspheres can be fluorescently-coded for multiplexing molecular analysis, but their usage has been limited by fluorescent quenching and bleaching and crowded spectral domain with issues of cross-talks and background interference. Each bioassay step of mixing and separation of analytes and reagents require off-line particle handling procedures. Here, we report that stray magnetic fields can code and decode a collection of hierarchically-assembled beads. By the microfluidic assembling of mesoscopic superparamagnetic cores, diverse and non-volatile stray magnetic field response can be built in the series of microscopic spheres, dumbbells, pears, chains and triangles. Remarkably, the set of stray magnetic field fingerprints are readily discerned by a compact giant magnetoresistance sensor for parallelised screening of multiple distinctive pathogenic DNAs. This opens up the magneto-multiplexing opportunity and could enable streamlined assays to incorporate magneto-mixing, washing, enrichment and separation of analytes. This strategy therefore suggests a potential point-of-care testing solution for efficient kinetic assays.